2021
DOI: 10.5194/hess-25-4995-2021
|View full text |Cite
|
Sign up to set email alerts
|

Sequential data assimilation for real-time probabilistic flood inundation mapping

Abstract: Abstract. Real-time probabilistic flood inundation mapping is crucial for flood risk warning and decision-making during the emergency period before an upcoming flood event. Considering the high uncertainties involved in the modeling of a nonlinear and complex flood event, providing a deterministic flood inundation map can be erroneous and misleading for reliable and timely decision-making. The conventional flood hazard maps provided for different return periods cannot also represent the actual dynamics of floo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 71 publications
(72 reference statements)
0
36
0
Order By: Relevance
“…This is mainly because of limited access to high spatiotemporal resolution remote sensing data needed for assimilation in HD modeling. As an alternative to remote sensing data, recent studies demonstrated that point-source observations can be assimilated and provide a robust characterization of uncertainty in HD models ( Annis et al., 2022 ; Jafarzadegan et al., 2021a ; Muñoz et al., 2022 ). Xu et al.…”
Section: Quantifying and Reducing Uncertaintiesmentioning
confidence: 99%
See 2 more Smart Citations
“…This is mainly because of limited access to high spatiotemporal resolution remote sensing data needed for assimilation in HD modeling. As an alternative to remote sensing data, recent studies demonstrated that point-source observations can be assimilated and provide a robust characterization of uncertainty in HD models ( Annis et al., 2022 ; Jafarzadegan et al., 2021a ; Muñoz et al., 2022 ). Xu et al.…”
Section: Quantifying and Reducing Uncertaintiesmentioning
confidence: 99%
“…(2017a , 2017b) used a Particle Filter technique to assimilate several point-source WL observations into two-dimensional (2D) HD models. Jafarzadegan et al. (2021a) introduced a DA framework that assimilates both discharge and WL while considering correlations among point-source observations.…”
Section: Quantifying and Reducing Uncertaintiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Makungu and Hughes, 2021) or large-scale flood forecasting (e.g. GloFAS, Alfieri et al, 2013;Jafarzadegan et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…By simulating the flow routing processes through river networks, they allow climate models to close the water budget at the global scale. Then, several applications have been developed based on RRMs, including studies on the impact of climate change on extreme flows (floods and droughts, see e.g., Hirabayashi et al (2013); Yamazaki et al (2018)), water resources monitoring (e.g., Makungu and Hughes , 2021) or large scale flood forecasting (e.g., GloFAS, Alfieri et al , 2013;Jafarzadegan et al , 2021).…”
Section: Introductionmentioning
confidence: 99%